Anionic organo-hydrogel electrolyte with enhanced ionic conductivity and balanced mechanical properties for flexible supercapacitors. Issue 20 (5th May 2022) - Yang, Ye; Wang, Kun-Peng; Zang, Qian; Shi, Qiqi; Wang, Yiwei; Xiao, Zhenyu; Zhang, Qi; Wang, Lei
Abstract : A "hexagon" organo-hydrogel electrolyte is prepared for flexible supercapacitors with an electrochemical performance, which exhibits superior abilities of conduction, stretchability, anti-freezing, flexibility and thermal stability. Abstract : It remains a challenge to create hydrogel electrolytes with balanced conductivity, mechanical robustness and flexible properties, not to mention being able to operate at wide temperatures and potential ranges. This fundamentally arises from the inevitable freezing and dissociation of abundant water molecules in the polymer matrix at sub-zero temperatures and high potential, respectively, which results in the degeneration of the electronic and mechanical performance. Herein, we introduce the anionic λ-carrageenan gels (LC) and ethylene glycol (EG) into a poly(vinyl alcohol) (PVA) hydrogel to obtain a stretchable and elastic organo-hydrogel with a fixed K + channel. It delivers high ionic conductivity of 8.3 S m −1 at room temperature, 3.18 S m −1 at −40 °C and 9.67 S m −1 at 60 °C, exhibiting a superior anti-freezing ability and thermal stability, which exceeds most of the previously reported results for conductive hydrogels and organo-hydrogels. As proof, the fabricated supercapacitor (SC) device exhibits a high specific capacitance (113.6 F g −1 at −40 °C and 331.8 F g −1 at 60 °C with a current density of 3 A g −1 ), outstanding energy density (24.3 W h kg −1 ) and a high potential window (up to 1.5 V). More impressively, the flexible device can power electronic watches in extremely harsh environments such as being compressed, bent, and then immersed in an ice bath and EG solution without packaging. Therefore, the anionic organo-hydrogel with fixed cation (K + ) channels reveals an efficient way to obtain a preeminent hydrogel electrolyte for high-performance flexible SCs.